A Descriptive Overview of Deviations From an Institutional Peripheral Vasopressor Protocol and Its Effects on Safety Across an Academic Health System - Daniel Shyu; Nicholas E. Ingraham; Bailey McCarville; Christopher A. Linke; Nicole Newman; Lianne K. Siegel; Jared A. Larson; Anna R. Benson; Kathryn M. Pendleton (Critical Care Explorations, 2026)
OBJECTIVES: This study characterized deviations from an institutional peripheral vasopressor protocol and assessed associated extravasation events. DESIGN: Retrospective observational study of electronic medical records data. SETTING: Ten hospitals in an academic health system from October 2020 to May 2023. PATIENTS: All admitted adult patients who received vasopressor infusions. INTERVENTIONS: Implementation of a peripheral vasopressor protocol in October 2020. MEASUREMENTS AND MAIN RESULTS: Three thousand five hundred eighteen patients were identified as having received peripheral vasopressors from October 2020 to May 2023, with 1258 patients suspected of having a deviation from the protocol. One hundred sixty-two patients were randomly selected for chart review, and 73 patients had confirmed deviation. Sixty-three (86.3%) exceeded the maximum allowed dose, 23 had multiple simultaneously infusing peripheral vasopressors, 13 had a peripheral vasopressor infusing longer than 24 hours, and 13 received peripheral vasopressin. Most deviations (79.4%) occurred due to worsening shock while waiting for central access. Extravasation occurred in 10 patients (13.7%), with three patients requiring phentolamine treatment. Fifty-six patients (76.7%) subsequently required central access for continued vasopressor support. In a secondary analysis of the original source population, 47 of 3518 patients (1.3%) received phentolamine for peripheral vasopressor extravasation, of whom the majority (72.4%) were protocol concordant at the time of extravasation. CONCLUSIONS: Deviations from a peripheral vasopressor protocol primarily involved exceeding the protocol dose limit in the setting of worsening shock while awaiting central access. Clinically significant extravasations were infrequent even among patients with protocol deviations and most treated extravasations occurred in protocol-concordant patients, supporting the overall safety of peripheral vasopressors.